The Winged : An Upper Missouri River Ethno-ornithology - Chandler, Kaitlyn; Field Murray, Wendi; Zedeño, María Nieves; Clements, Samrat; James, Robert (Robert B.) (Book collections on Project MUSE., 2017)
"Investigates social interactions between Native American groups and birds along the upper Missouri River in all their tangible and intangible expressions"--Provided by publisher.